Monoclonal antibodies constructed from COVID-19 convalescent memory B cells exhibit potent binding activity to MERS-CoV spike S2 subunit and other human coronaviruses - Peng, Yuan; Liu, Yongcheng; Hu, Yabin; Chang, Fangfang; Wu, Qian; Yang, Jing; Chen, Jun; Teng, Shishan; Zhang, Jian; He, Rongzhang; Wei, Youchuan; Bostina, Mihnea; et al. (Frontiers in Immunology, 2022)
Introduction The Middle East respiratory syndrome coronavirus (MERS-CoV) and the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are two highly contagious coronaviruses causing MERS and COVID-19, respectively, without an effective antiviral drug and a long-lasting vaccine. Approaches for diagnosis, therapeutics, prevention, etc., particularly for SARS-CoV-2 that is continually spreading and evolving, are urgently needed. Our previous study discovered that >60% of sera from convalescent COVID-19 individuals, but <8% from general population, showed binding activity against the MERS-CoV spike protein, indicating that SARS-CoV-2 infection boosted antibodies cross-reactive with MERS-CoV. Methods To generate antibodies specific to both SARS-CoV-2 and MERS-CoV, here we screened 60 COVID-19 convalescent sera against MERS-CoV spike extracellular domain and S1 and S2 subunits. We constructed and characterized monoclonal antibodies (mAbs) from COVID-19 convalescent memory B cells and examined their binding and neutralizing activities against human coronaviruses. Results and Discussion Of 60 convalescent serum samples, 34 showed binding activity against MERS-CoV S2, with endpoint titers positively correlated with the titers to SARS-CoV-2 S2. By sorting single memory B cells from COVID-19 convalescents, we constructed 38 mAbs and found that 11 mAbs showed binding activity with MERS-CoV S2, of which 9 mAbs showed potent cross-reactivity with all or a proportion of spike proteins of alphacoronaviruses (229E and NL63) and betacoronaviruses (SARS-CoV-1, SARS-CoV-2, OC43, and HKU1). Moreover, 5 mAbs also showed weak neutralization efficiency against MERS-CoV spike pseudovirus. Epitope analysis revealed that 3 and 8 mAbs bound to linear and conformational epitopes in MERS-CoV S2, respectively. In summary, we have constructed a panel of antibodies with broad-spectrum reactivity against all seven human coronaviruses, thus facilitating the development of diagnosis methods and vaccine design for multiple coronaviruses.